Model Sistem Informasi Pemesanan dan Produksi Berbasis Web Menggunakan Metode Agile - Taufik Hidayat; henderi henderi; Euis Nurninawati; Ruli Supriati (Jurnal Ilmiah Matrik, 2023)
This research discusses the ordering and production application model developed with the php programming language. The application model is developed with an agile method approach that suits the circumstances that suit the needs of application development quickly but still meets the needs of application owners and users. Data collection was carried out using observation methods, interviews, and literature studies. Data collection is carried out to find out the problems that occur, while observation activities on the ongoing process and PIECES-based analysis aim to confirm the problems to be solved through application development. Application development is carried out through the stages of analysis, design, development, and testing. The design stages are carried out using the Unified Modeling Language (UML) approach. The development stage is done using the php programming language with the codeigniter 3 framework and the mysql database with visual studio code as the text editor. In the final part, testing activities are carried out with a black box testing approach. The test results show that the developed application is functioning properly and in accordance with the development goals. The application of ordering and production applications produced in this study plays a positive role in improving business process performance, and increasing the satisfaction of application users and enterprise customers.